Canine parvovirus enteritis: epidemic situation analysis and perspectives - T. S. Galkina; A. К. Karaulov (Ветеринария сегодня)
Parvovirus enteritis is one of canine dangerous diseases which poses a particular concern for practitioners and dog owners around the world. Parvovirus type 2 (CPV-2) can affect dogs at any age, but puppies between 6 weeks and 6 months old are most susceptible to infection. One of the main biological properties of parvovirus is its continuous genetic evolution, which led to the replacement of the original virus type by new antigenic variants – CPV-2a, CPV-2b and CPV-2c. According to the literature data, all three variants of the virus are currently circulating in the domestic dog population worldwide. The paper presents analysis of the epidemic situation and seasonal occurrence of canine parvovirus enteritis in certain regions of the Russian Federation in 2017–2019. It was shown that parvovirus enteritis was ranked first among the registered infectious diseases of dogs and accounted for 37% during the study period. It has been established that the disease is registered all year round, but the frequency of disease cases depends on the season. Canine parvovirus infection mainly occurs in spring, late autumn and early winter, which is probably associated with changes in daily temperature during these periods and decreased animal resistance. Despite extensive vaccination, the main reason for the wide spread of the virus is either interference with maternal antibodies in vaccinated puppies or low level of immune protection in adult dogs.